2003
DOI: 10.1093/nar/gkg232
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting regulation of the murine Meg1/Grb10 and human GRB10 genes; roles of brain-specific promoters and mouse-specific CTCF-binding sites

Abstract: The imprinted mouse gene Meg1/Grb10 is expres sed from maternal alleles in almost all tissues and organs, except in the brain, where it is expressed biallelically, and the paternal allele is expressed preferentially in adulthood. In contrast, the human GRB10 gene shows equal biallelic expression in almost all tissues and organs, while it is almost always expressed paternally in the fetal brain. To elucidate the molecular mechanisms of the complex imprinting patterns among the different tissues and organs of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
100
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 35 publications
10
100
1
2
Order By: Relevance
“…Subsequent experiments in mice demonstrated that Grb10 is transcribed in neurons from a series of downstream alternative promoters, exclusively from the paternal allele (8,47). This paternal expression is conserved in the human brain (48).…”
Section: Paternal Grb10 Expression In Neurons Affects Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent experiments in mice demonstrated that Grb10 is transcribed in neurons from a series of downstream alternative promoters, exclusively from the paternal allele (8,47). This paternal expression is conserved in the human brain (48).…”
Section: Paternal Grb10 Expression In Neurons Affects Behaviormentioning
confidence: 99%
“…1). The region surrounding one of these alternative promoters has been identified as an ICR, which exhibits DNA methylation only on the maternal allele in all examined tissues (8). On the paternal allele, the unmethylated Grb10 ICR is bound by CCCTC-binding factor (CTCF), a multifunctional transcription factor, which is recruited in a DNA methylation-sensitive manner and has been implicated in the regulation of imprinted expression at other loci (Fig.…”
mentioning
confidence: 99%
“…CTCF has long been associated with genomic imprinting due to its selective binding of the unmethylated maternal allele of the Igf2/H19 ICR resulting in parent-of-origin-specific expression of Igf2 and H19 in mouse and human (Bell and Felsenfeld 2000;Hark et al 2000;Kanduri et al 2000;Fedoriw et al 2004;Szabo et al 2004). CTCF has been studied at several other imprinted loci, and it binds the unmethylated allele at the gDMRs of Rasgrf1, Peg13, Kcnq1ot1 (Yoon et al 2005;Fitzpatrick et al 2007;Singh et al 2011), and Grb10 (Hikichi et al 2003;Mukhopadhyay et al 2004). CTCF-mediated regulation is postulated to be one of two major control mechanisms operating at ICRs (Lewis and Reik 2006;Kim et al 2009).…”
mentioning
confidence: 99%
“…The differential use of alternative promoters appears to be a common theme. For example, the Grb10 gene is maternally expressed in most tissues, yet predominantly paternal in the brain (Arnaud et al 2003;Hikichi et al 2003). This is accomplished through the use of a hypomethylated paternal DMR that is capable of serving as a promoter in this state (Arnaud et al 2003;Hikichi et al 2003;Yamasaki-Ishizaki et al 2007;Sanz et al 2008).…”
Section: Tissue-specific Imprintingmentioning
confidence: 99%